Amphiregulin in cellular physiology, health, and disease: Potential use as a biomarker and therapeutic target. Issue 2 (26th October 2021) - Singh, Siddharth S.; Chauhan, Shashi B.; Kumar, Awnish; Kumar, Shashi; Engwerda, Christian R.; Sundar, Shyam; Kumar, Rajiv
Abstract: Amphiregulin (AREG), which acts as one of the ligands for epidermal receptor growth factor receptor (EGFR), plays a crucial role in tissue repair, inflammation, and immunity. AREG is synthesized as membrane‐anchored pre‐protein, and is excreted after proteolytic cleavage, and serves as an autocrine or paracrine factor. After engagement with the EGFR, AREG triggers a cascade of signaling events required for many cellular physiological processes including metabolism, cell cycle, and proliferation. Under different inflammatory and pathogenic conditions, AREG is expressed by various activated immune cells that orchestrate both tolerance and host resistance mechanisms. Several factors including xenobiotics, cytokines, and inflammatory lipids have been shown to trigger AREG gene expression and release. In this review, we discuss the structure, function, and regulation of AREG, its role in tissue repair, inflammation, and homeostasis as well as the potential of AREG as a biomarker and therapeutic target. Abstract : (1) Immune‐mediated resistance and tolerance mechanisms are critical components of host immune response. (2) In this context, Amphiregulin (AREG) has been identified as a key regulatory factor secreted by both innate and adaptive immune cells, which not only promote the host resistance to the pathogen but also assist in tissue repair and wound healing under different inflammatory conditions. (3) AREG can act as a biomarker and therapeutic target under different inflammatory conditions